A new sublingual formulation of zolpidem for the treatment of sleep-onset insomnia. (February 2012) - Staner, Luc; Danjou, Philippe; Luthringer, Remy
Insomnia is a very frequent complaint that periodically or permanently affects up to 60% of the general population. Valuable therapeutic options rely on pharmacological and nonpharmacological management of insomnia complaints. Zolpidem is one of the most popular hypnotic drugs used to treat insomnia. The drug was synthesized by Synthélabo Recherche in the early 1980s and has proved to be a suitable and well-tolerated drug, especially with regard to efficacy in sleep initiation. The present review focuses on an alternate delivery form of zolpidem, Edluar™, a new sublingual formulation of zolpidem that has been developed for the treatment of sleep-onset insomnia. Studies have shown that Edluar has a faster sleep-induction effect, whereas it did not differ from the oral formulation in terms of sleep maintenance or side effects. This review also discusses the mechanism of action of zolpidem and its pharmacokinetic profile in comparison to Edluar. Efficacy studies in specific settings (such as non-nightly use or use in combination with cognitive behavioral therapy) and particular safety issues encountered with zolpidem use are also discussed.